Child and adolescent development in your classroom chronological approach - Bergin, Christi Ann Crosby; Bergin, David Allen (Cengage, 2019)
"This book provides you with research-based strategies and guidelines for your classroom, whether you will be teaching children in infancy and toddlerhood, high school, or anywhere in between. You'll learn how child development concepts are applied to topics of interest and relevance to teachers, including classroom discipline, teacher-student relationships, increasing intelligence, and many others. Chapters use an easy to follow format, and diversity and multicultural issues are integrated throughout. Real-world vignettes bridge the distance between research and your classroom, helping you be better prepared to create an environment that promotes optimal development in all children. With its practical classroom-based focus, this text will help you view all students more positively, give you the tools to effectively guide them, and make teaching more enjoyable"--Provided by publisher.